Gradient Ti (C, N)-based metal ceramic material and preparation method thereof
By setting the gradient distribution of the three-layer structure in the Ti(C,N)-based cermet material, the problem of the contradiction between hardness and toughness in the high-speed cutting process is solved, and the material's high wear resistance and overall toughness are achieved.
Patent Information
- Application Number
- CN202411856688.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-09-10
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-28
AI Technical Summary
Ti(C,N)-based cermet materials have contradictions in hardness and toughness during high-speed cutting, resulting in limited service life and application promotion.
A gradient Ti(C,N)-based cermet material is used, and a three-layer structure is provided in the material to increase the mass percentage of the Ni+Co bonded phase in sequence to form a gradient distribution structure. This structure has special mechanical response behavior under the action of external loads, has thermal relief and heat dispersion characteristics, and regulates internal stress distribution.
The performance requirements of material surface wear resistance and overall strength are achieved, and the limitations of difficulty in taking into account toughness and wear resistance are avoided by adjusting components, optimizing volume content and coating.
Smart Images

Figure CN119710412A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of powder metallurgy, and in particular relates to a gradient Ti (C, N)-based metal ceramic material and a preparation method thereof. Background Art
[0002] High-speed cutting is a key technology for equipment manufacturing in the fields of aerospace, transportation, industrial production, etc., in which the cutting substrate is the foundation and core that affects efficient processing. Ti(C,N)-based cermets have the advantages of excellent red hardness, high wear resistance, high chemical stability, etc. They have great application prospects in extreme service environments and can meet the high-speed cutting requirements of difficult-to-process materials such as titanium alloys and high-temperature alloys.
[0003] At present, Ti(C,N)-based cutting tools generally adopt homogeneous or coating structures. The homogeneous structure has a contradiction between high hardness and high toughness, and the coating structure has the risk of coating peeling and matrix deformation failure, which seriously limits its service life and application promotion. Due to the difference in composition, there is a clear interface between the "core-ring" structure and the bonding phase in Ti(C,N)-based cermets. The difference in organization on both sides of the interface makes it difficult to achieve thermodynamic coexistence. At the same time, the orientation difference and atomic mismatch on both sides have an important influence on the mechanical behavior of the material under the thermal coupling. Its multiphase interface and weak interface bonding lead to increased stress and premature instability. The complex "core-ring" structure and its interface stress have become a bottleneck for further improvement of fracture strength and impact toughness. How to find a balance between hardness and toughness is a key problem that Ti(C,N)-based cermets need to solve urgently. Summary of the invention
[0004] The purpose of the present invention is to solve the problems existing in the background technology.
[0005] The invention provides a gradient Ti(C, N)-based metal ceramic material, which comprises a gradient distribution structure composed of a Ti(C, N) hard phase and a Ni+Co bonding phase, wherein the gradient structure comprises a first layer structure, a second layer structure and a third layer structure which are sequentially stacked, and the mass percentage of each component of the first layer structure in the gradient distribution structure is: Ti(C, N): 66.5%, Co: 9%, Ni: 9%, WC: 5%, MoC: 5%, TaC: 4%, NbC: 1%, CrC: 0.5%; the mass percentage of each component in the second layer structure is: Ti(C, N): 58%, Co: 14%, Ni: 14%, WC: 5%, MoC: 5%, TaC: 3%, NbC: 1%; the mass percentage of each component in the third layer structure is: Ti(C, N): 50%, Co: 20%, Ni: 20%, WC: 3%, MoC: 4%, TaC: 2.5%, CrC: 0.5%.
[0006] In some embodiments, the mass percentages of the Ni+Co binder phase from outside to inside are 18%, 28% and 40% respectively.
[0007] The present invention provides a method for preparing a gradient Ti(C,N)-based metal ceramic material, comprising the following steps:
[0008] S1: Obtain three groups of components, wherein the mass percentage of the first group of components is: Ti(C,N): 66.5%, Co: 9%, Ni: 9%, WC: 5%, MoC: 5%, TaC: 4%, NbC: 1%, CrC: 0.5%; the mass percentage of the second group of components is: Ti(C,N): 58%, Co: 14%, Ni: 14%, WC: 5%, MoC: 5%, TaC: 3%, NbC: 1%; the mass percentage of the third group of components is: Ti(C,N): 50%, Co: 20%, Ni: 20%, WC: 3%, MoC: 4%, TaC: 2.5%, CrC: 0.5%;
[0009] S2: wet-milling the components obtained in step S1 to obtain three kinds of Ti(C,N)-based mixed powder slurries;
[0010] S3: drying the Ti(C, N)-based mixed powder slurry obtained in step S2 respectively to obtain three kinds of Ti(C, N)-based mixed powders;
[0011] S4: adding PEG to the three Ti(C,N)-based mixed powders obtained in step S3, followed by heating and mechanical mixing to obtain three composite feeds with fluidity;
[0012] S5: Mechanically crushing the three composite feeds obtained in step S4, and the average particle size of the composite feeds is 3 mm;
[0013] S6: performing powder extrusion 3D printing on the three kinds of feed particles obtained in step S5 to obtain a gradient Ti (C, N) based metal ceramic 3D printed blank;
[0014] S7: Degreasing the gradient Ti(C, N)-based cermet 3D printed blank obtained in step S6 to obtain a gradient Ti(C, N)-based cermet degreased blank;
[0015] S8: Sintering the gradient Ti(C, N)-based cermet degreased blank obtained in step S7 to obtain a gradient Ti(C, N)-based cermet material.
[0016] In some embodiments, step S2 includes:
[0017] The three groups of components obtained in step S1 were immersed in anhydrous ethanol respectively, and PW with a mass fraction of 4% was added, and then ball-milled respectively to obtain three Ti(C,N)-based mixed powder slurries, wherein the ball-to-material ratio during the ball milling process was 6:1, the ball milling speed was 200-300 rpm, and the ball milling time was 20-48 h.
[0018] In some embodiments, step S3 includes:
[0019] The Ti(C, N)-based mixed powder slurry obtained in step S2 is placed in a vacuum infrared drying oven and dried separately to obtain three kinds of Ti(C, N)-based mixed powders, wherein the air pressure in the vacuum infrared drying oven is maintained at 0.2-0.4 atm and the drying temperature is 80-110°C.
[0021] In some embodiments, step S4 includes:
[0022] The three Ti(C,N)-based mixed powders obtained in step S3 are respectively heated to 135-160° C. in an internal mixer;
[0023] 5-8% by mass of PEG was added to three kinds of Ti(C,N)-based mixed powders respectively and mixed for 1 hour to obtain three kinds of feed materials with good fluidity.
[0024] In some embodiments, step S6 includes:
[0025] The three composite feeds obtained in step S5 are sequentially 3D printed to obtain gradient Ti(C,N)-based metal ceramic 3D printed blanks, wherein the screw extrusion temperature of the UPS-250DC 3D printer is set to 130-165°C, and the printing angle is set to 45°.
[0026] In some embodiments, step S7 includes:
[0027] The gradient Ti (C, N)-based metal ceramic 3D printed blank after step S6 is degreased in a constant temperature water bath to obtain a gradient Ti (C, N)-based metal ceramic degreased blank, wherein the degreasing temperature is set to 50-60°C, the degreasing time is set to 50-90h, and after degreasing, it is dried in a vacuum drying oven at 80°C for 3h.
[0028] In some embodiments, step S8 includes:
[0029] Negative pressure dewaxing treatment, the gradient Ti (C, N) based cermet degreased blank obtained in step S7 is placed in a vacuum sintering furnace, the vacuum sintering furnace is heated to 360-450°C, and kept warm for 2-3 hours;
[0030] Pre-sintering: heat the vacuum sintering furnace to 1000-1200°C and keep it warm for 1-2 hours;
[0031] High-temperature diffusion sintering: heat the vacuum sintering furnace to 1300-1350°C and keep it warm for 0.5-1h; then heat it to 1470-1540°C and keep it warm for 1-1.5h; cool the temperature in the vacuum furnace to below 1000°C at a cooling rate of 20°C / min, and then cool it with the furnace.
[0032] Beneficial effects:
[0033] The present application discloses a gradient Ti(C,N)-based metal ceramic material including a gradient distribution structure composed of a Ti(C,N) hard phase and a Ni+Co bonding phase, wherein the gradient structure includes a three-layer structure, wherein the mass percentages of the Ni+Co bonding phase from the outside to the inside are 18%, 28% and 40% respectively. In this way, the gradient material has a special mechanical response behavior under the action of an external load, has thermal relaxation and thermal dispersion characteristics, can regulate the internal stress distribution, and achieves the performance requirements of the material surface being wear-resistant and overall toughness, avoiding the limitation that it is difficult to take into account both toughness and wear resistance by adjusting components, optimizing volume content and coatings. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is the SEM morphology of the gradient Ti (C, N) based metal ceramic 3D printed blank in the embodiment of the present invention;
[0035] Figure 2 The cross-sectional SEM morphology of the gradient Ti(C,N)-based metal ceramic material in the embodiment of the present invention;
[0036] Figure 3 The SEM morphology of the fracture of the gradient Ti (C, N) based metal ceramic material in the embodiment of the present invention;
[0037] Figure 4 This is the cross-sectional SEM morphology of the gradient Ti(C,N)-based metal ceramic material in the comparative example of the present invention. DETAILED DESCRIPTION
[0038] In order to make the technical scheme of the present invention better understood by the persons skilled in the art, the technical scheme in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are only embodiments of a part of the present invention, rather than all embodiments. The following is only a preferred embodiment of the present invention. It should be noted that, without departing from the principle of the present invention, the gradient combination of the remaining components (formula) should also be regarded as the protection scope of the present invention.
[0039] Example 1
[0040] In this embodiment, it includes:
[0041] S1: Weigh three groups of components according to their mass percentage, among which the mass percentage of the first group of components is: Ti(C,N): 66.5%, Co: 9%, Ni: 9%, WC: 5%, MoC: 5%, TaC: 4%, NbC: 1%, CrC: 0.5%; the mass percentage of the second group of components is: Ti(C,N): 58%, Co: 14%, Ni: 14%, WC: 5%, MoC: 5%, TaC: 3%, NbC: 1%; the mass percentage of the third group of components is: Ti(C,N): 50%, Co: 20%, Ni: 20%, WC: 3%, MoC: 4%, TaC: 2.5%, CrC: 0.5%.
[0042] S2: The components of S1 were immersed in anhydrous ethanol respectively, and 4% PW was added, and mixed by roller ball milling. The grinding balls used were ZrO2 grinding balls, the ball-to-material ratio was 6:1, the ball milling speed was 200 rpm, and the ball milling time was 24 h.
[0043] S3: drying the Ti(C,N)-based mixed powder slurry obtained in step S2 in a vacuum infrared drying oven, with the air pressure maintained at 0.2 atm and the drying temperature at 80° C. to obtain a Ti(C,N)-based mixed powder;
[0044] S4: the Ti(C,N)-based mixed powder obtained in step S3 is placed in an internal mixer and heated to 135° C., 8% by mass of PEG is added, and mixed for 1 hour to obtain three feeds with good fluidity;
[0045] S5: Mechanically crushing the three composite feeds obtained in step S4, and the average particle size of the composite feeds is 3 mm;
[0046] S6: The three kinds of feed particles obtained in step S5 are subjected to powder extrusion 3D printing. The screw extrusion temperature in the UPS-250DC 3D printer is set to 165°C and the printing angle is 45° to obtain a gradient Ti (C, N)-based metal ceramic blank. The SEM morphology of the gradient Ti (C, N)-based metal ceramic 3D printed blank is as follows: Figure 1 shown.
[0047] S7: placing the gradient Ti(C, N)-based metal ceramic 3D printed blank obtained in step S6 in a constant temperature water bath for degreasing, using water as the degreasing medium, setting the degreasing temperature to 60° C., setting the degreasing time to 50 h, and drying in a vacuum drying oven at 80° C. for 3 h after degreasing to obtain a gradient Ti(C, N)-based metal ceramic degreasing blank;
[0048] S8: Sinter the gradient Ti(C,N)-based metal ceramic degreased blank obtained in step S7. The specific operation is as follows: in the first stage, negative pressure dewaxing treatment, the sintering furnace containing the green blank is heated to 360 and 420°C, and kept warm for 2.5 hours respectively; in the second stage, pre-sintering, first the vacuum sintering furnace containing the green blank is heated to 1000°C, and kept warm for 2 hours; in the third stage, high-temperature diffusion sintering, first the temperature is heated to 1300°C, and kept warm for 0.5 hours; heated to 1500°C, and kept warm for 1.5 hours; the temperature in the vacuum furnace is reduced to below 1000°C at a cooling rate of 20°C / min, and then cooled with the furnace. Finally, a gradient Ti(C,N)-based metal ceramic material is obtained. After sintering, the cross-sectional SEM morphology of the gradient Ti(C,N)-based metal ceramic material is as follows Figure 2 As shown, the fracture SEM morphology is as follows Figure 3 As shown. The interface contour of the gradient layer in the 3D printed blank is clearly visible, without common layered structural material defects such as delamination or interface cracks. After sintering, the interface between the material layers is tightly bonded, without obvious defects, and the microstructure is uniform. The difference in the composition of the gradient layer causes the "core-ring structure" to change from black core-gray ring to white core-gray ring. After testing, the average HV of the gradient Ti (C, N)-based metal ceramic material is 1760, and the K IC The average value is 8.5 MPa·m 1 / 2 , the TRS average value is 2047MPa.
[0049] Example 2
[0050] In this embodiment, it includes:
[0051] S1: Weigh three groups of components according to their mass percentage, among which the mass percentage of the first group of components is: Ti(C,N): 66.5%, Co: 9%, Ni: 9%, WC: 5%, MoC: 5%, TaC: 4%, NbC: 1%, CrC: 0.5%; the mass percentage of the second group of components is: Ti(C,N): 58%, Co: 14%, Ni: 14%, WC: 5%, MoC: 5%, TaC: 3%, NbC: 1%; the mass percentage of the third group of components is: Ti(C,N): 50%, Co: 20%, Ni: 20%, WC: 3%, MoC: 4%, TaC: 2.5%, CrC: 0.5%.
[0052] S2: The components of S1 were immersed in anhydrous ethanol respectively, and 4% PW was added, and the mixture was mixed by roller ball milling. The grinding balls used were ZrO2 grinding balls, the ball-to-material ratio was 6:1, the ball milling speed was 200 rpm, and the ball milling time was 48 h.
[0053] S3: drying the Ti(C, N)-based mixed powder slurry obtained in step S2 in a vacuum infrared drying oven, with the air pressure maintained at 0.4 atm and the drying temperature at 110° C. to obtain a Ti(C, N)-based mixed powder;
[0054] S4: the Ti(C,N)-based mixed powder obtained in step S3 is placed in an internal mixer and heated to 160° C., 5% by mass of PEG is added, and mixed for 1 hour to obtain three feeds with good fluidity;
[0055] S5: Mechanically crushing the three composite feeds obtained in step S4, and the average particle size of the composite feeds is 3 mm;
[0056] S6: performing powder extrusion 3D printing on the three kinds of feed particles obtained in step S5, setting the screw extrusion temperature in the UPS-250DC 3D printer to 150° C. and the printing angle to 45° to obtain a gradient Ti (C, N)-based metal ceramic 3D printed blank;
[0057] S7: placing the gradient Ti(C, N)-based metal ceramic 3D printed blank obtained in step S6 in a constant temperature water bath for degreasing, using water as the degreasing medium, setting the degreasing temperature to 50° C., setting the degreasing time to 90 h, and drying in a vacuum drying oven at 80° C. for 3 h after degreasing to obtain a gradient Ti(C, N)-based metal ceramic degreasing blank;
[0058] S8: Sintering the gradient Ti(C,N)-based metal ceramic degreased blank obtained in step S7, the specific operation is: the first stage, negative pressure dewaxing treatment, the sintering furnace containing the green blank is heated to 420°C, and kept warm for 3 hours; the second stage, pre-sintering, firstly, the vacuum sintering furnace containing the green blank is heated to 1200°C, and kept warm for 1 hour; the third stage, high-temperature diffusion sintering, firstly, the temperature is heated to 1320°C, and kept warm for 0.5 hour; then the temperature is heated to 1470°C, and kept warm for 1 hour; the temperature in the vacuum furnace is reduced to below 1000°C at a cooling rate of 20°C / min, and then cooled with the furnace, and finally the gradient Ti(C,N)-based metal ceramic material is obtained.
[0059] The SEM morphology of the gradient Ti (C, N) based metal ceramic 3D printed blank prepared in Example 2 and the material SEM morphology test results are similar to those of the gradient Ti (C, N) based metal ceramic material prepared in Example 1.
[0060] After testing, the average HV value of the gradient Ti(C,N) based metal ceramic material is 1752, K IC The average value is 8.4 MPa·m 1 / 2 , the TRS average value is 2042MPa.
[0061] Example 3
[0062] In this embodiment, it includes:
[0063] S1: Weigh three groups of components according to their mass percentage, among which the mass percentage of the first group of components is: Ti(C,N): 66.5%, Co: 9%, Ni: 9%, WC: 5%, MoC: 5%, TaC: 4%, NbC: 1%, CrC: 0.5%; the mass percentage of the second group of components is: Ti(C,N): 58%, Co: 14%, Ni: 14%, WC: 5%, MoC: 5%, TaC: 3%, NbC: 1%; the mass percentage of the third group of components is: Ti(C,N): 50%, Co: 20%, Ni: 20%, WC: 3%, MoC: 4%, TaC: 2.5%, CrC: 0.5%.
[0064] S2: The components of S1 were immersed in anhydrous ethanol respectively, and 4% PW was added, and mixed by roller ball milling. The grinding balls used were ZrO2 grinding balls, the ball-to-material ratio was 6:1, the ball milling speed was 300 rpm, and the ball milling time was 20 h.
[0065] S3: drying the Ti(C, N)-based mixed powder slurry obtained in step S2 in a vacuum infrared drying oven, with the air pressure maintained at 0.3 atm and the drying temperature at 100° C. to obtain a Ti(C, N)-based mixed powder;
[0066] S4: the Ti(C,N)-based mixed powder obtained in step S3 is placed in an internal mixer and heated to 150° C., 7% by mass of PEG is added, and mixed for 1 hour to obtain three feeds with good fluidity;
[0067] S5: Mechanically crushing the three composite feeds obtained in step S4, and the average particle size of the composite feeds is 3 mm;
[0068] S6: The three kinds of feed particles obtained in step S5 are subjected to powder extrusion 3D printing, the screw extrusion temperature of the UPS-250DC 3D printer is set to 135°C, and the printing angle is 45°, to obtain a gradient Ti (C, N) based metal ceramic 3D printed blank;
[0069] S7: placing the gradient Ti(C, N)-based metal ceramic 3D printed blank obtained in step S6 in a constant temperature water bath for degreasing, using water as the degreasing medium, setting the degreasing temperature to 50° C., setting the degreasing time to 72 h, and drying in a vacuum drying oven at 80° C. for 3 h after degreasing to obtain a gradient Ti(C, N)-based metal ceramic degreasing blank;
[0070] S8: Sintering the gradient Ti(C,N)-based metal ceramic degreased blank obtained in step S6, the specific operation is: the first stage, negative pressure dewaxing treatment, the sintering furnace containing the green blank is heated to 450°C and kept warm for 2 hours; the second stage, pre-sintering, firstly, the vacuum sintering furnace containing the green blank is heated to 1100°C and kept warm for 1.5 hours; the third stage, high-temperature diffusion sintering, firstly, the temperature is heated to 1350°C and kept warm for 1 hour; then the temperature is heated to 1500°C and kept warm for 1 hour; the temperature in the vacuum furnace is reduced to below 1000°C at a cooling rate of 20°C / min, and then cooled with the furnace, and finally the gradient Ti(C,N)-based metal ceramic material is obtained.
[0071] The SEM morphology of the gradient Ti (C, N)-based metal ceramic 3D printed blank prepared in Example 3 and the material SEM morphology test results are also similar to those of the gradient Ti (C, N)-based metal ceramic material prepared in Example 1.
[0072] After testing, the average HV value of the gradient Ti(C,N) based metal ceramic material is 1747, K IC The average value is 8.3MPa·m 1 / 2 , the TRS average value is 2029MPa.
[0073] The various properties of the gradient Ti (C, N)-based metal ceramic materials formed according to the above embodiments are not much different and are basically stable, which solves the contradiction between strength and toughness and wear resistance. The transition between gradient layers is obvious, and the interface between material layers is tightly bonded after sintering, without obvious defects, and the microstructure is uniform. A three-layer structure is set up, and the content of the bonding phase is increased in sequence. The purpose of this design is to improve the strength and toughness of the material. This layer (the outermost layer) has a low content of metal bonding phase, and the reduced bonding phase is replaced by Ti (C, N) in the metal ceramic that contributes more to the hardness. The purpose of the design is to increase the hardness of the metal ceramic surface and give the material excellent wear resistance. The second and third layers increase the content of the bonding phase in sequence, and the design purpose is to enhance the strength and toughness of the material. In addition, the role of the middle layer is to reduce the convection migration of the liquid phase during the sintering process (there are differences between the substances in the middle layer and other layers) to avoid weakening the gradient structure.
[0074] The 3D printing forming in this application is not easily affected by the adverse effects of gravity on the uniformity of the microstructure of the material, and the integrated forming of different materials can be achieved without a mold, breaking through the limitations of traditional powder metallurgy forming on product shape, size and gradient distribution. The powder extrusion 3D printing in this application does not involve the melting of materials, and can achieve high-precision control of gradient layer thickness, composition and uniformity, compared to the powder melting 3D printing in the current prior art.
[0075] Comparative Example 1
[0076] The difference between this comparative example 1 and the above-mentioned embodiment 1 is that the temperature of the third stage during the sintering process is 1300° C., and a gradient Ti (C, N)-based metal ceramic material is obtained. Figure 4 As shown, the structure of the obtained material is not dense, that is, if the temperature is too low during the sintering process, effective diffusion and reaction between atoms will not occur. Similarly, through experiments, it is easy to cause the overall deformation of the material if the sintering temperature is too high.
[0077] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the protection scope of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A gradient Ti(C,N)-based cermet material, characterized in that: The metal ceramic material includes a gradient distribution structure composed of a Ti(C, N) hard phase and a Ni+Co bonding phase, wherein the gradient structure includes a first layer structure, a second layer structure and a third layer structure which are stacked in sequence, and the mass percentage of each component in the first layer structure of the gradient distribution structure is: Ti(C, N): 66.5%, Co: 9%, Ni: 9%, WC: 5%, MoC: 5%, TaC: 4%, NbC: 1%, CrC: 0.5%; the mass percentage of each component in the second layer structure is: Ti(C, N): 58%, Co: 14%, Ni: 14%, WC: 5%, MoC: 5%, TaC: 3%, NbC: 1%; the mass percentage of each component in the third layer structure is: Ti(C, N): 50%, Co: 20%, Ni: 20%, WC: 3%, MoC: 4%, TaC: 2.5%, CrC: 0.5%.
2. The metal ceramic material according to claim 1, characterized in that: The mass percentages of Ni+Co bonding phase from outside to inside are 18%, 28% and 40% respectively.
3. A method for preparing a gradient Ti(C,N)-based metal ceramic material, characterized in that: The following steps are involved: S1: Obtain three groups of components, wherein the mass percentage of the first group of components is: Ti(C,N): 66.5%, Co: 9%, Ni: 9%, WC: 5%, MoC: 5%, TaC: 4%, NbC: 1%, CrC: 0.5%; the mass percentage of the second group of components is: Ti(C,N): 58%, Co: 14%, Ni: 14%, WC: 5%, MoC: 5%, TaC: 3%, NbC: 1%; the mass percentage of the third group of components is: Ti(C,N): 50%, Co: 20%, Ni: 20%, WC: 3%, MoC: 4%, TaC: 2.5%, CrC: 0.5%; S2: wet-milling the components obtained in step S1 to obtain three kinds of Ti(C,N)-based mixed powder slurries; S3: drying the Ti(C, N)-based mixed powder slurry obtained in step S2 respectively to obtain three kinds of Ti(C, N)-based mixed powders; S4: adding PEG to the three Ti(C,N)-based mixed powders obtained in step S3, followed by heating and mechanical mixing to obtain three composite feeds with fluidity; S5: Mechanically crushing the three composite feeds obtained in step S4, and the average particle size of the composite feeds is 3 mm; S6: performing powder extrusion 3D printing on the three composite feed materials obtained in step S5 to obtain a gradient Ti(C,N)-based metal ceramic 3D printed blank; S7: Degreasing the gradient Ti(C, N)-based metal ceramic formed blank obtained in step S6 to obtain a gradient Ti(C, N)-based metal ceramic degreased blank; S8: Sintering the gradient Ti(C, N)-based cermet degreased blank obtained in step S7 to obtain a gradient Ti(C, N)-based cermet material; Wherein, the step S6 comprises: The three composite feeds obtained in step S5 are 3D printed in sequence to obtain gradient Ti (C, N)-based metal ceramic 3D printed blanks, wherein the screw extrusion temperature of the UPS-250DC 3D printer is set to 130-165°C, and the printing angle is set to 45°.
4. The preparation method according to claim 3, characterized in that: The step S2 comprises: The three groups of components obtained in step S1 were immersed in anhydrous ethanol respectively, and PW with a mass fraction of 4% was added, and then ball-milled respectively to obtain three Ti(C,N)-based mixed powder slurries, wherein the ball-to-material ratio during the ball milling process was 6:1, the ball milling speed was 200-300 rpm, and the ball milling time was 20-48 h.
5. The preparation method according to claim 3, characterized in that: The step S3 comprises: The Ti(C,N)-based mixed powder slurry obtained in step S2 was placed in a vacuum infrared drying oven for drying to obtain three kinds of Ti(C,N)-based mixed powders, wherein the air pressure in the vacuum infrared drying oven was maintained at 0.2-0.4 atm and the drying temperature was 80-110°C.
6. The preparation method according to claim 3, characterized in that: The step S4 comprises: The three Ti(C,N)-based mixed powders obtained in step S3 are respectively heated to 135-160° C. in an internal mixer; 5-8% by mass of PEG was added to three kinds of Ti(C,N)-based mixed powders respectively and mixed for 1 hour to obtain three kinds of feed materials with good fluidity.
7. The preparation method according to claim 3, characterized in that: The step S7 comprises: The gradient Ti (C, N)-based metal ceramic formed blank after the treatment in step S6 is degreased in a constant temperature water bath to obtain a gradient Ti (C, N)-based metal ceramic degreased blank, wherein the degreasing temperature is set to 50-60°C, the degreasing time is set to 50-90h, and after degreasing, it is dried in a vacuum drying oven at 80°C for 3h.
8. The preparation method according to claim 3, characterized in that: The step S8 comprises: Negative pressure dewaxing treatment, the gradient Ti (C, N) based cermet degreased blank obtained in step S7 is placed in a vacuum sintering furnace, the vacuum sintering furnace is heated to 360-450°C, and kept warm for 2-3 hours; Pre-sintering: heat the vacuum sintering furnace to 1000-1200°C and keep it warm for 1-2 hours; High-temperature diffusion sintering: heat the vacuum sintering furnace to 1300-1350°C and keep it warm for 0.5-1h; then heat it to 1470-1540°C and keep it warm for 1-1.5h; cool the temperature in the vacuum furnace to below 1000°C at a cooling rate of 20°C / min, and then cool it with the furnace.